AN EXPERIMENTAL STUDY OF A CORDIERITE-BEARING GRANULITE FROM RUNDVAGSHETTA, LUTZOW-HOLM BAY, EAST ANTARCTICA - カワサキ, トシスケ; イシカワ, マサヒロ; モトヨシ, ヨウイチ; KAWASAKI, Toshisuke; ISHIKAWA, Masahiro; MOTOYOSHI, Yoichi (National Institute of Polar Research, 1994)
P(論文) This is a preliminary report on the high-pressure experimental confirmation of the solidus phases of a cordierite-bearing granulite (Sample No. RVH92011102A; T. KAWASAKI et al. : Proc. NIPR Symp. Antarct. Geosci., 6,47,1993) collected from Rundvagshetta, Lutzow-Holm Bay, East Antarctica. The constituent minerals of this granulite used as the starting material for the present experiments are sapphirine, cordierite, garnet, orthopyroxene, sillimanite, spinel, biotite, hornblende, K-feldspars, plagioclase, quartz and zircon. We found the decompressional reaction textures : (1) orthopyroxene and sillimanite are never in direct contact and are separated from each other by a canal of cordierite and/or cordierite+sapphirine; (2) garnet is locally replaced by a symplectite composed of orthopyroxene+cordierite+sapphirine±plagioclase. The peak metamorphic condition before decompression was estimated as 900℃ or more based on the initial orthopyroxene+sillimanite+garnet assemblage (T. KAWASAKI et al., 1993,ibid.). This granulite is chemically characterized by high MgO (18.74 wt%), extremely low CaO (0.4 wt%) and relatively high K_2O (3.34 wt%) contents. The value for Mg/(Fe+Mg) of the bulk rock is 0.764. These chemical features are reflected in the appearance of the norm corundum (10.4 wt%) and the norm olivine (34.8 wt%), the disappearance of the norm quartz and the norm diopside, and relatively high ratios of the norm orthoclase (19.7 wt%). High pressure experiments were carried out using a 16.0mm piston cylinder device at Kochi University. We employed talc+Pyrex glass as a pressure medium (T. KAWASAKI et al. : Island Arc, 2,228,1994). Cordierite is stable as a subsolidus phase in equilibrium with orthopyroxene, mica, rutile and plagioclase at 7 kbar and 850℃. At 10 kbar and 1000℃ this granulite partially melts in the presence of vapor, and the solidus assemblage is cordierite+orthopyroxene+mica+rutile+sapphirine+spinel. At 7 kbar and 1050℃ cordierite disappears, and the silicate melt contains about 69 wt% of ...